BIOGRAFI : ALLISMAWITA SEBAGAI PENDIRI SMK TEKNOLOGI PLUS PADANG (1996-2012) - Japika, Robin - (Pendidikan Sejarah, 2014)
This thesis discuss about Allismawita in build SMK Teknologi Plus in Belanti Indah,North Padang District, Padang City at 1996-2012. This study is needed to do because we can seehow the way that be done by Allismawita in build the vocational school (SMK), and to make easythis research, so the writer formulates the problems like : How the background of Allismawitaâslife, and her role in build SMK Teknologi Plus, and the last problem that will be discussed is howthe role of Allismawita in developing of SMK Teknologi Plus Padang from 1996 until 2012. Thus,the purpose of this research is to know the background of Allismawitaâs life, and to know her rolein build SMK Teknologi Plus, and the last is to know her role in developing SMK Teknologi Plusfrom 1996 until 2012. Method that be used in this research is method that appropriate with historyresearch which follow some steps like : (1) Heuristic, (2) Source Critic, (3) Analysis andInterpretation, (4) Historiography. Based on the result of the research that have been done, it canbe concluded that : beside, look the effort that done by Allismawita, the writer also do researchabout history of her life from childhood until married. And her effort in build SMK Teknologi Plusis not easy, there are some challenges that face by patient. In fact, all of her jobs fluency and herhopes also can release although the writer see how society view that pro and contra towardAllismawita, so that the result that Allismawitaâs build can be felt by society until now. It is likethe students who have graduated from that school is easy to get jobs, especially in machine andindustry that are in Indonesia and abroad.